September arhar holds promise for crop diversification in upland ecology of Bihar - Kumar, Rakesh; Kumar, Sanjeev; Krishna, Bal (Indian Farming, 2024)
North-East Plains (NEPs) experience both temporal and spatial variations in the rainfall intensity, often resulting in temporary waterlogging. This, in turn, leads to partial or complete mortality of pigeonpea seedlings during the rainy season. To address this issue, the adoption of September arhar planting presents as an alternative approach. In post-Green Revolution era, Indo-Gangetic Plains of India, encompassing parts of north-west and north-east plains, witnessed the widespread adoption of rice-wheat system. While this system has contributed to improved food and nutritional security, it has displaced grain legumes from the agricultural landscape. This continued reliance on rice-wheat system has been associated with numerous adverse effects on human health, soil quality, and environmental well-being.